Silver Leaching from Printed Circuit Board Using Deep Eutectic Solvent-Oxaline, Maline, and Succiline - Fatimah, Soja Siti; Mora, Abraham; Sumarna, Omay; Ramdaniah, Hudaifatul A. N (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2025)
The exponential growth in printed circuit boards (PCBs) waste, presents an urgent environmental and economic challenge. PCBs contain silver which has a high potential economic value. The high production of waste and the potential economic value make it important to recycle PCB waste. Recycling can be conducted by leaching silver using Deep Eutectic Solvent (DES). DES is environmentally friendly and able to form complexes with various types of metals. This research aims to study the effect of the HBD carbon chain length of oxalic acid, malonic acid, and succinic acid from choline chloride-based eutectic solvents (DES) on the efficiency of leaching silver from Printed Circuit Board (PCB) waste. Optimization of the solid/liquid ratio, time, and temperature is carried out to obtain optimum leaching conditions. The synthesis results show that DES oxaline 2:1, malin 1:1, and succilin 2:1 have good stability, forming a colorless, clear, and viscous solution. FTIR analysis shows a shift in the wave number of the -OH group due to hydrogen bond interactions between HBA and HBD molecules in the formation of DES. The leaching yield of DES against standard silver oxide was measured using AAS. DES oxaline 2:1 has the greatest efficiency compared to other DES variations. The results of optimizing standard silver leaching with DES oxaline showed that the S/L ratio was 40 mg/mL, with a time of 18 hours, at a temperature of 60°C which resulted in a recovery percentage of 90.90%, while for the PCB waste sample yielded an efficiency of 99.38%. The eutectic solvent oxaline has the potential to be an environmentally friendly solvent that is efficient in leaching silver from PCB electronic waste.